Ensuring safe school environments : exploring issues, seeking solutions - Fishbaugh, Mary Susan; Schroth, Gwen; Berkeley, Terry R. (Topics in educational leadership., 2003)
Ensuring Safe School Environments: Exploring Issues--Seeking Solutions presents research findings and information about school violence, with a focus on strategies for increasing school safety. Based on a special topical issue of Rural Special Education Quarterly, the original journal articles have been rewritten to address safe schools from the perspective of suburban and urban, as well as rural environments. Topics include the frequency of violence in these different settings; violence as it directly impacts school administrators; strategies for preventing and addressing violen.